Non-viral Gene Delivery Methods for Bone and Joints - Gantenbein, Benjamin; Tang, Shirley; Guerrero, Julien; Higuita-Castro, Natalia; Salazar-Puerta, Ana I.; Croft, Andreas S.; Gazdhar, Amiq; Purmessur, Devina (Frontiers in Bioengineering and Biotechnology, 2020)
Viral carrier transport efficiency of gene delivery is high, depending on the type of vector. However, viral delivery poses significant safety concerns such as inefficient/unpredictable reprogramming outcomes, genomic integration, as well as unwarranted immune responses and toxicity. Thus, non-viral gene delivery methods are more feasible for translation as these allow safer delivery of genes and can modulate gene expression transiently both in vivo, ex vivo, and in vitro. Based on current studies, the efficiency of these technologies appears to be more limited, but they are appealing for clinical translation. This review presents a summary of recent advancements in orthopedics, where primarily bone and joints from the musculoskeletal apparatus were targeted. In connective tissues, which are known to have a poor healing capacity, and have a relatively low cell-density, i.e., articular cartilage, bone, the intervertebral disc (IVD), and tendons, several approaches have recently been undertaken. We provide a brief overview of the existing technologies, using nano-spheres/engineered vesicles, lipofection, and in vivo electroporation. Here, delivery for microRNA (miRNA), and silencing RNA (siRNA) and DNA plasmids will be discussed. Recent studies will be summarised that aimed to improve regeneration of these tissues, involving the delivery of bone morphogenic proteins (BMPs), such as BMP2 for improvement of bone healing. For articular cartilage/osteochondral junction, non-viral methods concentrate on targeted delivery to chondrocytes or MSCs for tissue engineering-based approaches. Fewer studies have focused on tendons/ligaments or IVDs. For tendons, nano-particle delivery of growth factors has shown promise. For the IVD, growth factors such as GDF5 or GDF6 or developmental transcription factors such as Brachyury or FOXF1 seem to be of high clinical interest. However, the most efficient method of gene transfer is still elusive, as several preclinical studies have reported many different non-viral methods andclinical translation of these techniques still needs to be validated. Here we discuss the non-viral methods applied for bone and joint and propose methods that can be promising in clinical use.